Wild Flowers of Britain and Europe - Sterry, Paul and Press, Bob (New Holland Publishers London, 2004)
This guide identifies over 1200 species of wild flowers, offering detailed descriptions and colour illustrations. Its features include: an extensive introduction with practical advice; notes on field equipment; a discussion on conservation; and a list of areas of outstanding botanical interest.
Include Color Illustrations and Index
Keywords: Wild flowers -- Europe -- Great Britain